Population genetic structure of Phaedranassa cinerea Ravenna (Amaryllidaceae) and conservation implications - María Belén Buenaño; Carmen Ulloa Ulloa; Javier Francisco-Ortega; Alan W. Meerow; Nora H. Oleas (BMC Plant Biology)
Abstract Background Andean orography has shaped the endemism of plant species in montane forests, creating a mosaic of habitats in small and isolated areas. Understanding these endemic species' genetic diversity patterns is crucial for their conservation. Phaedranassa cinerea (Amaryllidaceae), a species restricted to the western Andes of Ecuador, is listed as “vulnerable” according to the IUCN criteria. This study seeks to determine whether there is genetic structure among and within Phaedranassa cinerea populations, estimate the timing of their genetic divergence, and recommend conservation strategies based on these genetic structure findings. Results Using 13 microsatellites and a Bayesian approach, we analyzed the genetic differentiation of P. cinerea and possible diversification scenarios. Our results indicate that the genetic diversity of P. cinerea is lower than congeneric species. The Bayesian analysis identified two genetic groups, with no evidence of isolation by distance. Populations in the northwest of the Ecuadorean Andes have less allele richness compared to those in the southwest. Additionally, the species exhibits excess homozygosity and evidence of bottlenecks. Our Bayesian analysis suggests that the differentiation among populations was not older than 5,000 years and was as recent as 600 years ago for some of the populations. Based on the geographic distribution of the known populations, the species should be listed as endangered instead of vulnerable to extinction. Conclusions Phaedranassa cinerea shows lower genetic diversity than related species, with the most variation within populations. We identified two to four genetic groups, suggesting recent divergence along the ridges of the western Andes. The findings suggest that conservation efforts should focus on securing genetic exchange between populations to preserve the genetic diversity of P. cinerea.